2011
DOI: 10.1101/gr.123745.111
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in TCF7L2 expression define its role as a key regulator of glucose metabolism

Abstract: Genome-wide association studies (GWAS) have consistently implicated noncoding variation within the TCF7L2 locus with type 2 diabetes (T2D) risk. While this locus represents the strongest genetic determinant for T2D risk in humans, it remains unclear how these noncoding variants affect disease etiology. To test the hypothesis that the T2D-associated interval harbors cis-regulatory elements controlling TCF7L2 expression, we conducted in vivo transgenic reporter assays to characterize the TCF7L2 regulatory landsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
146
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(164 citation statements)
references
References 39 publications
13
146
2
3
Order By: Relevance
“…Several studies have demonstrated the beneficial effect of TCF7L2 on ␤-cell proliferation, insulin secretion, and the expression of incretin hormone receptors (3,33,34). These findings, however, are in contradiction with the suggestion that TCF7L2 exerts deleterious effects on ␤-cells by other investigations (22,30). It has also been demonstrated that TCF7L2 type 2 diabetes risk SNPs are associated with elevated hepatic glucose production in individuals even during a hyperinsulinemic euglycemic clamp as well as during hepatic insulin resistance (22,28,39).…”
contrasting
confidence: 52%
See 1 more Smart Citation
“…Several studies have demonstrated the beneficial effect of TCF7L2 on ␤-cell proliferation, insulin secretion, and the expression of incretin hormone receptors (3,33,34). These findings, however, are in contradiction with the suggestion that TCF7L2 exerts deleterious effects on ␤-cells by other investigations (22,30). It has also been demonstrated that TCF7L2 type 2 diabetes risk SNPs are associated with elevated hepatic glucose production in individuals even during a hyperinsulinemic euglycemic clamp as well as during hepatic insulin resistance (22,28,39).…”
contrasting
confidence: 52%
“…However, the functional role of TCF7L2 in pancreatic islets remains unclear and controversial (3,19,22,30,33,34). Because TCF7L2 is also expressed in organs other than pancreatic islets, including liver, brain, muscle, and fat tissues, which are likewise important in metabolic homeostasis, it is necessary to define the function of TCF7L2 and further study the metabolic function of Wnt signaling in each of those organs.…”
Section: Discussionmentioning
confidence: 99%
“…Human carriers of the TCF7L2 rs7903146 risk allele have increased pancreatic islet size, and altered alpha:beta cell ratios and distribution within pancreatic islets [6]. DNA sequences around the TCF7L2 rs7903146 SNP contain regulatory elements that are critical in the regulation of TCF7L2 transcription, suggesting that the type 2 diabetes susceptibility conferred by this locus is related to modified TCF7L2 expression [7]. At least 20 different TCF7L2 splice variants and isoforms exist (Table 1) [8][9][10][11][12], which may also differ in their transcriptional activation properties [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Although several investigations suggested that TCF7L2 negatively regulates hepatic gluconeogenesis (8,10,11,17), one recent study (7) reported that liver-specific knockout of TCF7L2 reduced hepatic glucose production (HGP), while hepatic overexpression of TCF7L2 increased HGP. As a result, the controversial issues surrounding the metabolic function of TCF7L2 have been extended from pancreatic b-cells to liver and hepatocytes specifically (4)(5)(6)9,13,(18)(19)(20). TCF7L2 or other transcription factor (TCF) members can interact with b-catenin (b-cat), forming the bipartite transcription factor b-cat/TCF, which serves as the important effector of the Wnt signaling pathway.…”
mentioning
confidence: 99%
“…Following pivotal studies indicating that the transcription factor 7-like 2 (TCF7L2) is an important risk gene for the development of type 2 diabetes (T2D) (1), great efforts have been made to explore its role as a Wnt signaling molecule in pancreatic b-cells and other tissues including liver (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Although several investigations suggested that TCF7L2 negatively regulates hepatic gluconeogenesis (8,10,11,17), one recent study (7) reported that liver-specific knockout of TCF7L2 reduced hepatic glucose production (HGP), while hepatic overexpression of TCF7L2 increased HGP.…”
mentioning
confidence: 99%